Membangun Kesadaran Siswa Tentang Mitigasi Bencana Gempa Bumi Melalui Program Edukasi - Dhohirrobbi, Achmad; Islamudin, Mohamad Mujahid; Chamidah, Nur; Amin, Saiful (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Indonesia is highly vulnerable to natural disasters, particularly earthquakes, due to its location at the convergence of three major tectonic plates. Every year, various disasters occur, significantly impacting communities, especially children who are the most vulnerable group. This community service program aims to improve the earthquake disaster mitigation understanding of students at Asrama Tahfidz Al Uswah Bangil through an integrated learning method that combines theory and practice. The program includes introducing earthquake signs, self-rescue actions, as well as simulations of pre-disaster, during disaster, and post-disaster earthquake responses. The earthquake simulation provides students with hands-on experience in taking correct actions during disasters. Activities are carried out by dividing students into small groups to enhance interaction, communication, and collective understanding among them. After the material presentation, a Higher Order Thinking Skills (HOTS) based quiz is conducted to assess students' comprehension of the material presented. It is hoped that the knowledge and skills gained by students through this program will help them be more prepared and vigilant in facing potential disasters. This activity also contributes to increasing public awareness of the importance of disaster mitigation in Indonesia, with the hope that students can become change agents in their communities regarding disaster preparedness.